Feasibility of the mobile mindfulness‐based stress reduction for breast cancer (mMBSR(BC)) program for symptom improvement among breast cancer survivors. Issue 2 (8th August 2017) - Lengacher, Cecile A.; Reich, Richard R.; Ramesar, Sophia; Alinat, Carissa B.; Moscoso, Manolete; Cousin, Lakeshia; Marino, Victoria R.; Elias, Maya N.; Paterson, Carly L.; Pleasant, Michelle L.; Rodriguez, Carmen S.; Wang, Hsiao‐Lan; et al.
Abstract: Objective: The purpose of this pilot study was to test the feasibility of delivering the mobile mindfulness‐based stress reduction for breast cancer (mMBSR(BC)) program using an iPad and to evaluate its impact on symptom improvement. Methods: A single group, pre‐posttest design was implemented among female stages 0‐III breast cancer survivors (BCS) who completed treatment. Data were collected at baseline and week 6 on measures of psychological and physical symptoms and quality of life. The mMBSR(BC) program is a standardized, stress‐reducing intervention that combines sitting and walking meditation, body scan, and yoga and is designed to deliver weekly 2‐hour sessions for 6 weeks using an iPad. Results: The mean age of the 15 enrolled BCS was 57 years; one participant was non‐Hispanic black, and 14 were non‐Hispanic white. Of the 13 who completed the study, there were significant improvements from baseline to 6 weeks post‐mMBSR(BC) in psychological and physical symptoms of depression, state anxiety, stress, fear of recurrence, sleep quality, fatigue, and quality of life ( P 's < .05). Effect sizes for improvements of multiple symptoms ranged from medium to large. Conclusions: These results provide preliminary support that the mMBSR(BC) program may be feasible and acceptable, showing a clinical impact on decreasing psychological and physical symptoms. This mobile‐based program offers a delivery of a standardized MBSR(BC) intervention to BCS that is convenient for their own schedule while decreasing symptom burden in the survivorship phase after treatment for breast cancer.